Comparative evaluation of conventional with endoscopy assisted nasal septal correction surgery in a tertiary care teaching hospital Trichy - Anwar M., Mohamed; A., Jesudoss; P., Thirumalaikolundusubramanian (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Nasal septal deviation is of both congenital and traumatic etiology, found among children and adults and many of whom require corrective surgery. Recently endoscopy assisted nasal septal correction surgery is being performed in many centers as a preferred one. Hence it was decided to find out the postoperative outcomes among those who underwent both the types of surgical procedures. Methods: A total of 50 patients with septal deviation underwent conventional surgery and another 50 operated with endoscopy assisted method were considered for this study. Both groups were followed up for postoperative outcomes and relief of symptoms after 48 hours, 8 weeks and 24 weeks for statistical analysis. Results: Head ache, watering of eyes and nasal obstruction were found significantly less in endoscopy assisted nasal septal correction during the first 48 hours and 8 weeks when compared with conventional surgery and it became negligible after 24 weeks of postoperative period. Conclusions: Endoscopy assisted surgery is convenient in targeting the surgical site with less trauma and less requirement of time to perform the surgery. However, the initial cost would be higher for installation of endoscopy and maintenance.